(untitled) (Journal of the Management Sciences, 2024)
This study investigated the impact of Board composition on the profitability of commercial banks in Nigeria. It adopted Ex-post facto research design comprising of data obtained from secondary sources. This data were obtained from the audited annual report of 13 out of 14 commercial banks quoted on the Nigerian Exchange Group between the life span of 2013- 2022. Regression analysis was used to analyse the data collected for the study and the study revealed and concluded that Board composition has a positive and insignificant impact on the profitability of commercial banks in Nigeria (β= 0.003, p-value = 0.326) hence it recommends that commercial banks should carefully monitor all fundamentals that indicate profitability issues, and not merely focus on firm attributes; since the firm’s attributes do not completely isolate firms from profitability threats. It also recommends that commercial banks should equally compose their board based on proficiency and skill requirements, among others rather than size.